Reciprocal Regulation of Abl and Receptor Tyrosine Kinases - Srinivasan, Divyamani (2009)
Previously, we showed that Abl kinases (c-Abl, Arg) are activated downstream of PDGF in a manner dependent on Src kinases and PLC-γ1, and promote PDGF-mediated proliferation and migration of fibroblasts. We additionally demonstrated that Abl kinases bind directly to PDGFR-β via their SH2 domains. In this study, we extend these findings by demonstrating that Abl kinases also are activated downstream of a PDGF autocrine growth loop in glioblastoma cells, indicating that the PDGFR-Abl signaling pathway also is likely to be important in glioblastoma development and/or progression. We recently showed that Abl kinases are highly active in many breast cancer cell lines, and the Her-2 receptor tyrosine kinase contributes to cAbl and Arg kinase activation. In this study, we show that Abl kinase SH2 domains bind directly to Her-2, and like PDGFR-β, Her-2 directly phosphorylates c-Abl. Previously, we demonstrated that PDGFR-β directly phosphorylates Abl kinases in vitro, and Abl kinases reciprocally phosphorylate PDGFR-β. Here, we show that PDGFR-β–phosphorylation of Abl kinases has functional consequences as PDGFR-β phosphorylates Abl kinases on Y245 and Y412, sites known to be required for activation of Abl kinases. Moreover, PDGFR-β phosphorylates Arg on two additional unique sites whose function is unknown. Importantly, we also show that Abl-dependent phosphorylation of PDGFR-β also has functional and biological significances. c-Abl phosphorylates three tyrosine residues on PDGFR-β (Y686, Y934, Y970), while Arg only phosphorylates Y686. Y686 and Y934 reside in PDGFR-β catalytic domains, while Y970 is in the C-terminal tail. Using site-directed mutagenesis, we show that Abl-dependent phosphorylation of PDGFR-β activates PDGFR-β activity, in vitro, but serves to downregulate PDGFR-mediated chemotaxis. These data are exciting as they indicate that Abl kinases not only are activated by PDGFR and promote PDGFR-mediated proliferation and migration, but also act in an intricate negative feedback loop to turn-off PDGFR-mediated chemotaxis.